Pengembangan Identitas Islam Indonesia melalui Strategi Branding Humas Museum Islam Indonesia K. H Hasyim Asy’ari Jombang - Lungita Elok Iktikafia; Rakhmad Saiful Ramadhani; Fatihatul Lailiyah (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
This research aims to analyze the branding strategy implemented by the Public Relations (PR) division of the Museum of Islamic Indonesia K.H. Hasyim Asy’ari (MINHA) in developing the identity of Indonesian Islam. Using a descriptive qualitative approach, data were obtained through observation, interviews, and documentation. The analysis applies Sicco Van Gelder’s brand strategy theory, which consists of three main dimensions: brand positioning, brand identity, and brand personality. The findings indicate that MINHA’s PR strategically and consistently implements branding through three key aspects: organizing public events, utilizing social media, and incorporating architectural design to reinforce the identity of Indonesian Islam. These strategies have successfully shaped the museum’s image as inclusive, educational, and youth-friendly, presenting a moderate and tolerant face of Indonesian Islam. The role of PR extends beyond promotion to become a driving force in conveying the narrative of Indonesian Islam through adaptive communication approaches. This study recommends optimizing additional digital platforms and developing an official website to further strengthen the museum’s branding on a broader scale.